2007
DOI: 10.1002/hep.21699
|View full text |Cite
|
Sign up to set email alerts
|

Sodium retention and ascites formation in a cholestatic mice model: Role of aldosterone and mineralocorticoid receptor?

Abstract: Renal sodium retention in experimental liver cirrhosis originates from the distal nephron sensitive to aldosterone. The aims of this study were to (1) determine the exact site of sodium retention along the aldosterone-sensitive distal nephron, and (2) to evaluate the role of aldosterone and mineralocorticoid receptor activation in this process. Liver cirrhosis was induced by bile duct ligation in either adrenalintact or corticosteroid-clamped mice. Corticosteroid-clamp was achieved through adrenalectomy and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…We showed previously, that bile duct-ligated mice developed ascites concomitantly to Na,K-ATPase stimulation in cortical collecting ducts exclusively [1]. Underlining the role of the aldosterone sensitive distal nephron in ascites development, studies performed with rats showed an increased apical targeting of ENaC in ascitic animals [20,21].…”
Section: Introductionmentioning
confidence: 88%
“…We showed previously, that bile duct-ligated mice developed ascites concomitantly to Na,K-ATPase stimulation in cortical collecting ducts exclusively [1]. Underlining the role of the aldosterone sensitive distal nephron in ascites development, studies performed with rats showed an increased apical targeting of ENaC in ascitic animals [20,21].…”
Section: Introductionmentioning
confidence: 88%
“…SGK1-dependent renal salt retention favor the development of edema during treatment with PPARγ agonists [166] or in nephrotic syndrome [135]. Furthermore, increased SGK1 expression has been found during ascites formation in cirrhotic rats [167]. …”
Section: The Role Of Sgk1 In Renal Function and Salt Appetitementioning
confidence: 99%
“…Peritoneal fluid was always present when hepatotoxins were administered via the intraperitoneal route, but extensive intra-abdominal adhesions occurred in the majority of mice precluding a correct evaluation of ascites. An alternative model of cirrhosis is represented by BDL, which is also associated to a high mortality rate and induces histological changes that are quite different from those observed in the human form of disease [11][12][13]. Although the BDL model ultimately leads to decompensation, ascites can scarcely be assessed due to the occurrence of post-surgical intraperitoneal adhesions [11].…”
Section: Introductionmentioning
confidence: 98%